Article Commentary: Defining New Directions for More Effective Management of Surgical Pain in the United States: Highlights of the Inaugural Surgical Pain Congress™. Issue 3 (March 2014) - Joshi, Girish P.; Beck, David E.; Emerson, Roger Hill; Halaszynski, Thomas M.; Jahr, Jonathan S.; Lipman, Arthur G.; Nihira, Mikio A.; Sheth, Ketan R.; Simpson, Melanie H.; Sinatra, Raymond S.
Despite advances in pharmacologic options for the management of surgical pain, there appears to have been little or no overall improvement over the last two decades in the level of pain experienced by patients. The importance of adequate and effective surgical pain management, however, is clear, because inadequate pain control 1) has a wide range of undesirable physiologic and immunologic effects; 2) is associated with poor surgical outcomes; 3) has increased probability of readmission; and 4) adversely affects the overall cost of care as well as patient satisfaction. There is a clear unmet need for a national surgical pain management consensus task force to raise awareness and develop best practice guidelines for improving surgical pain management, patient safety, patient satisfaction, rapid postsurgical recovery, and health economic outcomes. To comprehensively address this need, the multidisciplinary Surgical Pain Congress™ has been established. The inaugural meeting of this Congress (March 8 to 10, 2013, Celebration, Florida) evaluated the current surgical pain management paradigm and identified key components of best practices.